MOBILESCHOOL CONCEPTUAL MODEL FOR SECONDARY SCHOOL - HASHIM, AHMAD SOBRI (2014)
Mobile learning management system (MLMS) refers to the utilization of mobile devices in managing academic related activities. In this research, there are two main problems that have been identified; lack of research in terms of investigating the effectiveness of teaching and learning using MLMS and lack ofm-leaming theories or concepts incorporation for the development of MLMS especially for secondary school. Therefore, this study aims to fulfil four main objectives; to identifY variables to solve the identified problems, to develop a conceptual model for MLMS called MobileSchool, to develop MLMS called MobileSchool system, and to evaluate MobileSchool system in terms of usability and effectiveness.